Educação terapêutica : do âmbito do sintoma ao prazer de viver e significar - possiblidades pedagógicas - Felker, Cinthia Caino (2008)
The Therapeutic Education, implemented in the Public Net of Teaching in the state of Rio Grande do Sul has been a pedagogical alternative that worries in helping to emerge a subject of desire, capable of social conviviality, having in Psychoanalytic Theory the main subsidy of orientation. In a wider manner, the pedagogic practices during that period of time (paradigm) have been based upon the teachings of the Historical-Cultural Theory that proposes, through the use of mediated action and through interaction, a learning viability for those students who present psychical difficulties. Both the Psychoanalytic and the Historical-Cultural Theories consider language function as exercising a main role in the constitution of a subject, in the same way that it is considered as the center of the alteration in the psychopathologic manifestations (in the Psychoanalysis Lacanian interpretation). The problem that it imposes suggested that each of the theoretical references that drive us (professors) into that educational activity, understands the constitution of the subject (through language) in different manners, sometimes derived from the parental relationships (Psychoanalytic Theory), other times from environmental exchanges (Historical-cultural Theory). In the view of such divergence it is necessary to review the (im)possibilities of connection among those theoretical presuppositions, and, in order to obtained results that reflected the reality of the theory-practice association that guided the present study, it was considered the professionals speeches that carried out such an educational action